Penerapan Analisis Spasial pada Proses Pemantauan Pengobatan pada Kejadian Kesehatan Jiwa di Kabupaten Grobogan - Sutiyono; Riniasih , Wahyu; Suryani; Kumalasari , Nurya; Makmun, Muhammad; Temu, Sri (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
This community service aimed to implement strategies to address mental health disorders in Grobogan Regency through education and application of mental health dissemination in the community. The methods employed included counseling techniques with mental health education and direct field implementation. Activities were conducted in the villages of Toroh District in July 2024, encompassing location surveys, obtaining permits, socialization, method discussions, and documentation. The results indicated successful problem identification and solution implementation, including the role of families in supporting mental health. Education provided insights into family functions, such as problem identification, decision-making regarding treatment, and utilization of healthcare services. All activity targets, including the effectiveness of demonstration methods, were achieved 100%. Sustainability aspects covered education, social benefits, and economic impacts, such as the increased productivity of healthy individuals contributing to economic growth. In conclusion, the mental health education initiative was successfully received by the community with a good understanding, fostering a willingness to apply mental health strategies. This program has the potential to be sustainable, supporting the community's educational, social, and economic aspects.